2009
DOI: 10.1097/ccm.0b013e3181b6f727
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of muscle strength in the intensive care unit

Abstract: Traditional (indirect) techniques, such as electromyography and nerve conduction velocity measurement, do not reliably predict intensive care unit-acquired muscle weakness and its clinical consequences. Therefore, quantitative assessment of skeletal muscle force is important for diagnosis of intensive care unit-acquired motor dysfunction. There are a number of ways for assessing objectively muscle strength, which can be categorized as techniques that quantify maximum voluntary contraction force and those that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 113 publications
(109 reference statements)
1
37
0
8
Order By: Relevance
“…[33][34][35] An association between ICU-acquired muscle weakness and pharyngeal dysphagia leading to aspiration likely contributes to such poor clinical outcomes. Notably, aspiration does not always lead to pathology and can remain asymptomatic or "silent."…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] An association between ICU-acquired muscle weakness and pharyngeal dysphagia leading to aspiration likely contributes to such poor clinical outcomes. Notably, aspiration does not always lead to pathology and can remain asymptomatic or "silent."…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a pediatric progressive mobility protocol administered to 25 medical/surgical PICU patients aged 3 to 18 years using cycle ergometry and/or interactive video gaming interventions in the PICU is practical [69]. Neither of the described pediatric studies reported any adverse events despite 50% to 52% of children being mechanically ventilated while receiving the intervention [68,69].…”
Section: Pediatric Mobilizationmentioning
confidence: 99%
“…B. auch im Rahmen eines täglichen Aufwachversuchs) lässt sich eine erworbene Muskelschwäche recht frühzeitig mit Hilfe der Handdynamometrie oder aber durch die Beurteilung des Kraftgrades anhand der Medical-Research-Council(MRC)-Skala feststellen [7,62]. Dabei gelten bei der Handdynamometrie der dominanten Seite Kraftwerte < 11 kg bei Männern bzw.…”
Section: E Es Mehren Sich Die Hinweise Dass Eine Exakte Differenzierunclassified